- #1
Jncik
- 103
- 0
Homework Statement
solve uxx = utt
The Attempt at a Solution
using the method of separation of variables I get
X''(x) - λ*X(x) = 0
T''(t) - λ*Τ(t) = 0
For λ = 0 I get X(x) = Ax + B where A and B are constants
T(t) = Dt + E where D and E are constants
hence u(x,t) = (Ax + B)*(Dt + E)
for λ>0 I get u(x,t) = [PLAIN]http://img690.imageshack.us/img690/8068/asdqu.gif [/URL] where c1,c2,C1,C2 constants
for λ = -b^2<0 I get (E*cos(bx) + F*sin(bx))*(G*cos(bt) + H*sin(bt)) where E,F,G,H constants
hence the solution
is from the superposition principle
u(x,t) = (Ax + B)*(Dt + E) + [PLAIN]http://img690.imageshack.us/img690/8068/asdqu.gif [/URL] + (E*cos(bx) + F*sin(bx))*(G*cos(bt) + H*sin(bt))please is this correct? i think its wrong, because I am not sure about the last part
also our professor has only the [PLAIN]http://img690.imageshack.us/img690/8068/asdqu.gif [/URL] as a reply, but i think its wrong, because we have to check for all λ to find all the possible solutions
Last edited by a moderator: